1998
DOI: 10.1136/jech.52.5.293
|View full text |Cite
|
Sign up to set email alerts
|

Socio-cultural factors in maternal morbidity and mortality: a study of a semi-urban community in southern Nigeria

Abstract: Study objective-To understand community based or socio-cultural factors that determine maternal morbidity and mortality in a semi-urban setting. Design-The study is an exploratory multidisciplinary operations research and the instruments were focus groups and interviews. Setting-Ekpoma, a semi-urban community with a population of 70 000 in central part of Edo state in southern Nigeria. Participants-Thirteen groups of women, two groups of men, and two groups of traditional birth attendants. Results-There is a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 2 publications
0
43
0
Order By: Relevance
“…Similar observations have been noted in previous studies. [7,8] Surprisingly, this high level of awareness even among some sections of the populace does not translate to reduced maternal mortality rates, as Nigeria still has one of the worst statistics in the world with regard to maternal mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar observations have been noted in previous studies. [7,8] Surprisingly, this high level of awareness even among some sections of the populace does not translate to reduced maternal mortality rates, as Nigeria still has one of the worst statistics in the world with regard to maternal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[2,3,5,10] Okolocha et al found that women in southern Nigeria had fairly good knowledge of obstetric hemorrhage as a cause of maternal mortality but yet their attitudes, practices and situations kept them away from, or delayed the decision to seek, modern obstetric care. [7] Causes such as infidelity, witchcraft/evil forces and disobedience surprisingly constituted 8.3% of the causes of death mentioned by the subjects. This may be due to the fact that majority of the study population were educated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregnancy outcomes rank among the pressing reproductive health problems in the world. Globally, an annual estimate of 600 000 women aged 15-49 die of pregnancy related causes, with 99 % coming from the developing world (1)(2)(3) and Nigeria alone accounting for 10 % of this total (4) . The status of maternal and fetal mortality may be threatening and calls for serious attention.…”
Section: Need For Improved Maternal Nutrition For Successful Pregnancmentioning
confidence: 99%